(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper, the system for data hiding in audio-video using anti forensics technique for authentication and data security is designed by using 32-bit ARM controller for image, audio and image steganography. The embedded system will help to secure the message with in the audio and video file. In Embedded system, the message much secure because even though if the unauthorized person succeeds in being able to hack the image, the person will not able to read the message as well as acquire the information in the audio file. Secret data like image and audio is encrypted into cover data by developing the application involved with LSB algorithm on ARM architecture device.